Problematizations of Discretion Policy in Indonesia’s Administration Law Number 30 of 2014 - Wahyudi, Andi (Research and Development Agency Ministry of Home Affairs, 2017)
This paper aims to discuss problematizations of discretion issue in the Administration Law 2014. Discretion is one of some discussed issues in the Administration Law which provides a legal guidance for bureaucrats to conduct their jobs. Drawing on Bacchi’s WPR (What is problem represented to be?) approach to policy analysis, this paper interrogates what ‘problem(s)’ is (are) produced in the policy document, what presuppositions are used as arguments to support the ‘problems’, what left as unproblematic issue that is absence in the policy problematizations, and what effects are produced by the ‘problem’ representation. The paper finds out that rules and procedures are the key concepts which assumed as policy ‘problems’ related to discretion issue. Neglecting the certain rules and procedures will be considered as doing illegal action. Only public managers have the discretionary power or managerial discretion, but in a limited room, because of upper manager’s intervention. However, this discretion policy remains an inefficient and rigid process in facing certain situation because, in exercising discretion, they have to obey certain rules and procedures. In addition, staffs do not have discretionary authority within their jobs although they might also face some certain situation which needs to make decisions.